Fluid Shear Stress and Fibroblast Growth Factor-2 Increase Endothelial Cell-Associated Vitronectin. (1st June 2017) - Mathew, Justin G.; Basehore, Sarah; Clyne, Alisa Morss
Abstract : Vitronectin is a matricellular protein that plays an important role in both coagulation and angiogenesis through its effects on cell adhesion and the plasminogen system. Vitronectin is known to bind to endothelial cells upon integrin activation. However, the effect of integrin activation by shear stress and growth factors on cell-associated vitronectin and plasminogen system activity has not yet been studied. We therefore exposed human umbilical vein endothelial cells to steady laminar flow, oscillating disturbed flow, or fibroblast growth factor-2 (FGF-2) for 24 hours. We then measured cell-associated vitronectin by Western blot and plasminogen system activity using a Chromozym assay. Steady laminar flow, oscillating disturbed flow, and FGF-2 all increased cell-associated vitronectin, although the vitronectin molecular weight varied among the different conditions. FGF-2 also increased cell-associated vitronectin in microvascular endothelial cells and vascular smooth muscle cells. The increase in cell-associated vitronectin increased plasminogen system activity. Confocal microscopy showed that vitronectin was primarily located in the basal and intracellular regions. α v β 5 integrin inhibition via genistein, an anti- α v β 5 antibody, or β 5 siRNA knockdown abrogated the FGF-2-induced increase in cell-associated vitronectin and increased plasminogen system activity. These data show that shear stress and growth factors increase cell-associated vitronectin through integrin activation, which may affect coagulation and angiogenesis.